Using human-centered design to develop a nurse-to-family telehealth intervention for pediatric transfers - Jennifer L Rosenthal; Audriana Ketchersid; Elva Horath; April Sanders; Thomas A Harper; Adrienne E Hoyt-Austin; Sarah C Haynes (Digital Health, 2023)
Objective To develop a nurse-to-family telehealth intervention for pediatric inter-facility transfers using the human-centered design approach. Methods We conducted the inspiration and ideation phases of a human-centered design process from July 2022 to December 2022. For the inspiration phase, we conducted a qualitative cross-sectional case study design over 3 months. We used thematic analysis with the framework approach of parent and provider interviews. Five team members individually coded transcripts and then met to discuss memos, update a construct summary sheet, and identify emerging themes. The team adapted themes into “How Might We” statements. For the ideation phase, multidisciplinary stakeholders brainstormed solutions to the “How Might We” statements in a design workshop. Workshop findings informed the design of a nurse-to-family telehealth intervention, which was iteratively revised over 2 months based on stakeholder feedback sessions. Results We conducted interviews with nine parents, 11 nurses, and 13 physicians. Four themes emerged supporting the promise of a nurse-to-family telehealth intervention, the need to effectively communicate the intervention purpose, the value of a user-friendly workflow, and the essentiality of ensuring that diverse populations equitably benefit from the intervention. “How Might We” statements were discussed among 22 total workshop participants. Iterative adaptations were made to the intervention until feedback from workshop participants and 67 other stakeholders supported no further improvements were needed. Conclusion Human-centered design phases facilitated stakeholder engagement in developing a nurse-to-family telehealth intervention. This intervention will be tested in an implementation phase as a feasibility and pilot trial.